The Collaboration between Dior and Balinese Endek Woven within The Framework of Indonesian Cultural Diplomacy - Dewi, Putu Ratih Kumala; Wiranata, I Made Anom (Global Strategis, 2023)
Endek Bali has received world attention after a well-known fashion company from France, Dior, used Balinese endek woven fabric in its 2021 SpringSummer collection. Using the concepts of cultural diplomacy and nation branding and employing qualitative method, this study aims to explain the use of Balinese endek in supporting Indonesia’s nation branding through collaboration with Dior. The data was collected through in-depth interviews, literature studies, as well as thorough analysis of official statements collected from the Bali provincial government and the Ministry of Foreign Affairs of the Republic of Indonesia. The study shows that the Indonesian government plays an important role in facilitating Indonesian cultural diplomacy using Balinese endek woven, which was carried out in colaboration with Christian Dior, where the Indonesian government act as a communicator between the fashion brand and the endek weavers, marking a pattern of cultural diplomacy relations between the government and the private sector, which further strengthen Indonesia’s nation branding as a culturally rich country with creative human resources. Keywords: Christian Dior, Cultural Heritage, Diplomacy, Endek Bali, Nation Branding Tenun endek Bali mendapat perhatian dunia setelah perusahaan fesyen ternama asal Perancis, Dior, menggunakan kain tenun endek Bali sebagai koleksi tahun 2021 untuk busana musim semi dan musim panas. Dengan menggunakan konsep diplomasi budaya dan nation branding serta metode kualitatif, penelitian ini bertujuan menjelaskan penggunaan tenun endek Bali dalam menunjang nation branding Indonesia melalui kolaborasi dengan Christian Dior. Pengumpulan data dilakukan melalui proses wawancara, studi literatur terkait, serta analisis pernyataan resmi pemerintah provinsi Bali dan Kementerian Luar Negeri. Hasil penelitian menunjukkan bahwa Pemerintah Indonesia memiliki peranan penting dalam memfasilitasi diplomasi budaya Indonesia menggunakan tenun endek Bali yang dilakukan melalui kolaborasi dengan Dior, membentuk pola hubungan diplomasi kebudayaan antara pemerintah dan sektor swasta, yang lebih lanjut memperkuat nation branding Indonesia sebagai negara yang kaya ragam budaya dan sumber daya manusia kreatif. Kata-kata kunci: Christian Dior, Diplomasi, Endek Bali, Nation Branding, Warisan Budaya